Experience in Using Temporary Crowns Made According to a Digital Protocol for Prosthetics of Vital Teeth (Clinical Case) - Skibitsky, В.; Zakharova, Г. (Actual Dentistry, 2025)
Abstract. The article focuses on the clinical applications of temporary crowns manufactured using CAD/CAM technology for the long-term protection of teeth with vital pulp. The authors present a clinical case of patient N, who underwent reconstructive dental prosthetics with crowns designed and manufactured using a digital protocol. Study purpose. Evaluation of the clinical effectiveness of using temporary crowns made by 3D modeling and milling on prepared vital teeth. Materials and methods. Clinical observation for one month on the condition of the condition of six vital maxillary teeth prepared for all-ceramic crowns with immediate coverage by milled provisional crowns. Radiovisiography, 3D tomography, and electroodontodiagnostics were used for the initial and repeated examination. Radiovisiography, 3D tomography, and electroodontodiagnostics were used for the initial and repeated examination of the teeth. Intraoral scanning and Exocad software were utilized to assess occlusal relationships, plan, and design prosthetic devices. Provisional crowns were fabricated using 3D milling (Mill Box software (CIM system), DG shape milling machine (Roland) and fixed with RelyX Temp NE (3M ESPE) temporary cement. Results. During the observation period, all teeth showed normal pulp electrical excitability, no clinical or radiological changes in the periodontium, and no complaints of discomfort in the prepared teeth or unsatisfactory fixation of the prosthetic structures. Conclusions. Temporary crowns made using the CAD/CAM system by milling can be recommended for the restoration of teeth with vital pulp.